Resurrection of the spider genus Bucliona Benoit, 1977, with a description of a new species from Kenya (Araneae, Clubionidae) - Zhang, Jianshuang; Marusik, Yuri M.; Oketch, Ambata D.; Kioko, Esther N.; Yu, Hao; Li, Shuqiang (Zootaxa, 2021)
The monotypic genus Bucliona Benoit, 1977 (type Clubiona dubia O. Pickard-Cambridge, 1870 from Saint Helena Island), previously considered a junior synonym of Clubiona Latreille, 1804, is resurrected. Three species are assigned to the genus Bucliona: B. dubia comb. reval., B. kirilli sp. n. (♂, Kenya), and B. jucunda (Karsch, 1879) comb. n., ex Clubiona (♂♀, Far East Asia).